Efektivitas Pengendalian Internal Kredit pada KPRI Universitas Jember - W. Wasito; Khusnul Khotimah; Septarina Prita DS (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
The rapid development of cooperative demands the internal control to be more accurate. The Employees Cooperative Republic of Indonesia of Jember University (KP-RI UNEJ) has increased the quantity and time period for provision credit. The aim of this study was to determine whether the implementation of the internal control of credit at KPRI UNEJ using COSO has been running effectively. This research employed descriptive analysis method in which the researcher used interview, observation and documentation instruments in collecting data. Moreover, data collected was tested the validity by using triangulation technique and Miles Hubberman method. As the result, the research showed that the internal control of KP-RI UNEJ has worked well. Althought there are some constraints and weaknesess that occurred in the USP(Saving and loan unit) such as adding human resources and information system updates. But overall the internal control of credit at KPRI has run effective.Keywords: COSO, Credit, Effectiveness, Internal Control.